Analisis Efektivitas Realisasi Anggaran Belanja Daerah Pada Setda Kota Magelang Bagian Administrasi Pembangunan - Fian Dwi Rahayu; Deni Ramdani (Universitas Hamzanwadi, 2021)
This study aims to determine and analyze the effectiveness of the realization of the expenditure budget at the Regional Secretariat of the City of Magelang Development Administration in 2017-2019. Type of descriptive research that was studied quantitatively. The source of the data used in this study is secondary data in the form of the Realization of the Regional Budget Setda Magelang Document of the Development Administration Section. Data collection techniques carried out by interviews, documentation, and study of literature. The results showed that the realization of the expenditure budget in the activity program of the Regional Secretariat of the City of Magelang Development Administration for the period of 2017-2019 was quite effective. However, the calculation of the growth in expenditure realization shows that the total budget realization from year to year tends to decrease